REPRESENTASI NILAI SOSIAL DALAM CERPEN “ORANG-ORANG ANEH DARI SELATAN” KARYA NI KOMANG ARIANI : Kajian Sosiologi Sastra terhadap Nilai-Nilai Sosial dalam Karya Sastra Kontemporer - Marlina Marlina; Suhartini Khalik; M. Nurzin R. Kasau (UNIVERSITAS PGRI YOGYAKARTA, 2026)
Literary works are a form of creative expression of authors that contain various life values, such as religious, social, cultural, and moral values, which contribute to character formation and can be used as a learning tool. Literature has a close relationship with people's lives because it is able to reflect social reality and life dynamics through the experiences of characters and the conflicts presented. This study aims to reveal the representation of social values ​​in the short story